Integrating Sustainability with Celebrity Endorser and Brand Image: Effects on Buying Interest in Cosmetics Consumers - Surjono, Welly; Purnamawati, Hilda; Sukiman, Iyan; Hafdriani , Al-nissya (ADPEBI International Journal of Business and Social Science, 2025)
Purpose – This study aims to find out how endorsements, and endorsements of elebrities and brands, can influence purchase preference. Methodology/approach–The research design in this study is quantitative with a self-administered online survey research method. The research participants were adult female cosmetics consumers over 18 years of age selected through online panel providers in Pangalengan, South Bandung, totaling 9,964 people with the Simple Random Sampling technique obtained 384 samples. Data analysis was conducted using descriptive statistics and inferential statistics, including t-test and ANOVA. Findings–The results reveal significant differences between the variables, and support plays an important role in purchasing decisions. ANOVA results show a strong relationship between endorsement, celebrity endorsement, and brand image. Regression models show that endorsements and celebrity endorsements positively affect purchase intentions, with endorsements having a relatively significant effect. Novelty/value –The integration between sustainability and the use of celebrity endorsers has not been explored in depth. Usually, celebrity endorsement focuses more on celebrity appeal, credibility, or social influence without considering sustainability.